Biological Activities of Extracts from Aerial Parts of Salvia pachyphylla Epling Ex Munz - Almada Taylor, Gabriela; Díaz Rubio, Laura; Salazar Aranda, Ricardo; Waksman de Torres, Noemí; Uranga Solis, Carla; Delgadillo Rodríguez, José; Ramos, Marco; Padrón, José; Hernández Martínez, Rufina; Córdova Guerrero, Iván (2018)
Abstract: The antioxidant, antimicrobial, antiproliferative, and enzyme inhibitory properties of ﬁve extracts from aerial parts of Salvia pachyphylla Epling ex Munz were examined to assess the prospective of this plant as a source of natural products with therapeutic potential. These properties were analyzed by performing a set of standard assays. The extract obtained with dichloromethane showed the most variety of components, as they yielded promising results in all completed assays. Furthermore,theextractobtainedwithethylacetateexhibitedthegreatestantioxidantactivity,aswell as the best xanthine oxidase inhibitory activity. Remarkably, both extracts obtained with n-hexane or dichloromethane revealed signiﬁcant antimicrobial activity against the Gram-positive bacteria; additionally, they showed greater antiproliferative activity against three representative cell lines of the most common types of cancers in women worldwide, and against a cell line that exempliﬁes cancers that typically develop drug resistance. Despite that, other extracts were less active, such as the methanolic or aqueous; their results are promising for the isolation and identiﬁcation of novel bioactive molecules.